2018
DOI: 10.1038/s41598-018-22751-6
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM study of the reaction mechanism of sulfite oxidase

Abstract: Sulfite oxidase is a mononuclear molybdenum enzyme that oxidises sulfite to sulfate in many organisms, including man. Three different reaction mechanisms have been suggested, based on experimental and computational studies. Here, we study all three with combined quantum mechanical (QM) and molecular mechanical (QM/MM) methods, including calculations with large basis sets, very large QM regions (803 atoms) and QM/MM free-energy perturbations. Our results show that the enzyme is set up to follow a mechanism in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…w MM is a weighting factor needed because the empirical potential of crystallographic refinement software is normally based on a statistical analysis of high-resolution crystal structures [37], rather than on energetic consideration (as for the QM term). We have shown that quantum refinement can locally improve crystal structures [31], decide protonation state of metal-bound ligands [38][39][40][41], oxidation state of metal sites [42,43] and protein ligands [41], detect photoreduction of metal ions [42,44,45] and decide what is really seen in crystal structures [44][45][46].…”
Section: Methodsmentioning
confidence: 99%
“…w MM is a weighting factor needed because the empirical potential of crystallographic refinement software is normally based on a statistical analysis of high-resolution crystal structures [37], rather than on energetic consideration (as for the QM term). We have shown that quantum refinement can locally improve crystal structures [31], decide protonation state of metal-bound ligands [38][39][40][41], oxidation state of metal sites [42,43] and protein ligands [41], detect photoreduction of metal ions [42,44,45] and decide what is really seen in crystal structures [44][45][46].…”
Section: Methodsmentioning
confidence: 99%
“…sulfite oxidase. Based on our recent QM-cluster (Van Severen et al, 2014 ) and QM/MM (Caldararu et al, 2018 ) studies, we considered the S → OMo mechanism, in which the S atom of the sulfite substrate attacks the equatorial oxo group of Mo VI , directly forming a Mo IV -sulfate intermediate (Im), via a first transition state TS1 (Figure 2 ). The sulfate product then dissociates into the second coordination sphere of the Mo ion via a second transition state (TS2).…”
Section: Resultsmentioning
confidence: 99%
“…The second test system was sulfite oxidase. The calculations were taken from our recent study of this enzyme (Caldararu et al, 2018 ). The active site contains a Mo ion coordinated to a molybdopterin (MPT) molecule, as well as a Cys residue and two oxo groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations